ANALISIS BEBAN KERJA ADMINISTRASI DAN DAMPAKNYA TERHADAP KINERJA PERENCANAAN DI WORKSHOP PT K2B - Arifin Ilham Akbar; Ahmad Firman Hakim (Adiba Aisha Amira, 2026)
This study aims to determine whether PT K2B is experiencing a shortage of staff in the administration, Ccr Workshop, and wasingman sections within the Planner division. In addition, a measurement of the workload in each section under the Planner division was also carried out. This study evaluates the workload in these positions at PT K2B by applying the Workload Analysis method using the Full-Time Equivalent (FTE) approach. Through observation, interviews, and analysis of operational documents for the period May 2026. The results of the study indicate that no excessive workload was found in the three sections under the Planner division. This study also serves as a mandatory report to fulfil a course requirement, and aims to provide data-based recommendations for the optimisation of human resources and workflow efficiency in the PT K2B workshop